Bad Health Informatics Can Kill – Is Evaluation the Answer? - Ammenwerth, E.; Shaw, N. T. (Methods of Information in Medicine, 2005)
Objective: Health care is entering the age of information society. It is evident that the use of modern information and communication technology (ICT) offers tremendous opportunities to improve health care. However, there are also hazards associated with ICT in health care. We want to present an overview of typical hazards associated with ICT in health care, and to discuss how ICT evaluation can be a solution.Methods: We analyze examples of failures and problems associated with ICT in health care. This collection is also made available on a website.Results and Conclusion: Systematic, continuous evaluation of quality and effects of ICT during the whole life cycle of ICT components seems to be one important approach to detect and prevent possible ICT hazards and failures, supporting a higher quality of patient care. However, empirical studies proving this assumption are needed.
Keywords: Health informatics; technology assessment; evaluation